Micronized progesterone: several aspects of miscarriage prophylaxis - N A Osipova (IP Berlin A.V., 2014)
Progesterone is an essential hormone in the process of reproduction. Progesterone offers an effective intervention when the continuation of pregnancy is at risk from immunological factors, luteinic and neuroendocrine deficiencies, and myometrial hypercontractility. Progesterone has been successfully used as prophylaxis in the prevention of spontaneous miscarriage, with treatment beginning from the first trimester of pregnancy. There is substantial evidence, too, to indicate that women with idiopathic recurrent miscarriage may benefit from the immunomodulatory properties of progesterone in early pregnancy. The use of progesterone has been extensively studied in the prevention of preterm birth in a variety of settings. This paper reviews the evidence for the safety and efficacy of the use of progesterone in each of these indications.